Provocative questions in osteosarcoma basic and translational biology: a report from the Children's Oncology Group - Roberts, Ryan D.; Kölsche, Christian (Cancer, 2019)
Patients who are diagnosed with osteosarcoma (OS) today receive the same therapy that patients have received over the last 4 decades. Extensive efforts to identify more effective or less toxic regimens have proved disappointing. As we enter a postgenomic era in which we now recognize OS not as a cancer of mutations but as one defined by p53 loss, chromosomal complexity, copy number alteration, and profound heterogeneity, emerging threads of discovery leave many hopeful that an improving understanding of biology will drive discoveries that improve clinical care. Under the organization of the Bone Tumor Biology Committee of the Children's Oncology Group, a team of clinicians and scientists sought to define the state of the science and to identify questions that, if answered, have the greatest potential to drive fundamental clinical advances. Having discussed these questions in a series of meetings, each led by invited experts, we distilled these conversations into a series of seven Provocative Questions. These include questions about the molecular events that trigger oncogenesis, the genomic and epigenomic drivers of disease, the biology of lung metastasis, research models that best predict clinical outcomes, and processes for translating findings into clinical trials. Here, we briefly present each Provocative Question, review the current scientific evidence, note the immediate opportunities, and speculate on the impact that answered questions might have on the field. We do so with an intent to provide a framework around which investigators can build programs and collaborations to tackle the hardest problems and to establish research priorities for those developing policies and providing funding.
Gesehen am 24.10.2019